Discus (Canaridiscus) laurisilvae sp. nov., a species from the laurel forest of La Gomera, Canary Islands (Gastropoda: Pulmonata: Discidae) - Allgaier, Christoph; Klemm, Matthias (Zootaxa, 2012)
A new endemic land snail species of the family Discidae, Atlantica (Canaridiscus) saproxylophaga Alonso, G. Holyoak & Yanes 2011, was recently described from La Gomera, Canary Islands (in Yanes et al. 2011). According to Rähle & Allgaier (2011) it is provisorily considered as belonging to the genus Discus. This species lives in the laurel forest and has the largest shell of all the Discidae hitherto known from Macaronesia. In the same habitat where D. saproxylophagus lives, we found individuals of similar size belonging to a second species of the taxon Canaridiscus. These two species show clear differences with respect to both shell morphology and genital anatomy, as described herein.